The Hollywood war film : Critical observations from World War I to Iraq - Binns, Daniel (Intellect Ltd, 2017)
Combining action, violence, and deeply conflicted emotions, war has always been a topic made for the big screen. Daniel Binns considers how war has been depicted throughout the history of cinema. Looking at depictions of both world wars, the Vietnam War, and the major conflicts in the Middle East, Binns reflects on representations of war and conflict, revealing how Hollywood has made the war film more than just a genre, but a dynamic cultural phenomenon. Looking closely at films such as All Quiet on the Western Front, Full Metal Jacket, and The Hurt Locker, Binns reveals the commonalities in Hollywood films despite the distinct conflicts and eras they represent, and he shows how contemporary war films closely echo earlier films in their nationalistic and idealistic depictions. Offering a trenchant analysis of some of the most important war films from the past century, this book will be of interest to anyone who has been captivated by how film has dealt with one of humanity's most difficult, but far too common, realities.